FOXP3+ regulatory T cells are associated with the severity and prognosis of sarcoidosis - Patterson, Karen C.; Miller, Wallace T.; Hancock, Wayne W.; Akimova, Tatiana (Frontiers in Immunology, 2023)
Rationale: Sarcoidosis is an inflammatory granulomatous disease of unknown etiology with predominant lung involvement. Organ involvement and disease severity, as well as the nature of immune alterations, vary among patients leading to a range of clinical phenotypes and outcomes. Our objective was to evaluate the association of disease course and immune responses in pulmonary sarcoidosis. Methods: In this prospective cohort study of 30 subjects, most of whom were followed for one year, we evaluated 14 inflammatory markers in plasma, 13 Treg/T cell flow cytometry markers and 8 parameters of FOXP3 + Treg biology, including suppressive function, epigenetic features and stability. Results: We identified a set of 13 immunological parameters that differ in sarcoidosis subjects in comparison with healthy donors. Five of those were inversely correlated with suppressive function of Tregs in sarcoidosis, and six (TNFα, TNFR I and II, sCD25, Ki-67 and number of Tregs) were particularly upregulated or increased in subjects with thoracic lymphadenopathy. Treg suppressive function was significantly lower in patients with thoracic lymphadenopathy, and in patients with higher burdens of pulmonary and systemic symptoms. A combination of five inflammatory markers, Ki-67 expression, Treg function, and lung diffusion capacity evaluated at study entry predicted need for therapy at one year follow-up in 90% of cases. Conclusion: Tregs may suppress ongoing inflammation at local and systemic levels, and TNFα, TNFR I and II, sCD25 and Ki-67 emerge as attractive biomarkers for in vivo sarcoid inflammatory activity.